PROPRIEDADES VIBRACIONAIS E TRANSIÇÃO DE FASE DO PIROCLORO Bi₂Sn₂O₇ - Silva, Rosivaldo Xavier da (2012)
In this work we investigated the vibrational, structural and dielectric properties of pyrochlore Bi2Sn2O7 (BSO) by Raman spectroscopy, differential scanning calorimetry (DSC) and infrared specular reflectance. The Raman spectrum of BSO was obtained as a function of temperature in the range from 23°C to 427°C. It was observed 18 broad Raman bands at room temperature (α phase) which have been classified according to the literature. The investigation of the evolution of the position, width, integrated area and intensity on the Raman modes depending on the temperature allowed estimating the temperature of the structural transition BSO α ( ) → β ( ) by approximately 127°C. The thermogram obtained by DSC under heating rates of 10K/min and 20K/min showed a peak with onset enthalpy at 98°C. Such peak was associated with the loss of structural domains discussed in the literature. Furthermore, theoretical calculations indicate that the observed peak is related to a displacive phase transition. The infrared reflectance spectrum was obtained at room temperature in the range 60 4000 cm-1, whose setting allowed us to identify the frequencies of transverse and longitudinal optical phonons which were also classified based on the literature. It was estimated the static dielectric constant, the dielectric losses tanδј and quality factor Q for the BSO in the microwave region. The dispersion parameters numerically obtained by Kramers - Kronig show to be in agreement with results obtained from the reflectance fitting.